2020
DOI: 10.4103/nmj.nmj_140_19
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, knowledge, and perception of the national health insurance scheme among national youth service corp members in Kano, Nigeria

Abstract: Background: The lofty objectives of the National Youth Service Corp (NYSC) are not only predicated on healthy graduates of tertiary institutions but also graduates who are confident in making informed health-related decisions. Therefore, Corp members' awareness, knowledge, and perception of the National Health Insurance Scheme (NHIS) and its programs become imperative. Materials and Methods: This was a cross-sectional study involving 203 participants selected by conveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A previous literature review mentioned how to propagate health among rural women and highlighted the importance of understanding population's perceptions, wants and needs (Qutab & Road, 2022). Health insurance education campaigns by accredited health-care facilities and national health insurance management institutions were needed to enhance low-adequate knowledge of health insurance among National Youth Service Corp Members in Kano, Nigeria (Michael et al, 2020). Knowledge about the procedure and regulation of health insurance is one part that forms the health insurance literacy of individuals (Ståhl et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…A previous literature review mentioned how to propagate health among rural women and highlighted the importance of understanding population's perceptions, wants and needs (Qutab & Road, 2022). Health insurance education campaigns by accredited health-care facilities and national health insurance management institutions were needed to enhance low-adequate knowledge of health insurance among National Youth Service Corp Members in Kano, Nigeria (Michael et al, 2020). Knowledge about the procedure and regulation of health insurance is one part that forms the health insurance literacy of individuals (Ståhl et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…For example, females were found to be comparatively more satisfied with healthcare services under insurance programs in Nigeria (Adewole et al, 2020). Most people were found to have limited information about their insurance programs in Nigeria (Michael et al, 2020). These past findings are very similar to the findings in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies with the same study population have shown comparable results. 3,9 This age range is among the most active in society, and any health issues could lead to lost man-hours and negative economic impacts. For a productive economy, it is essential to keep these age groups healthy throughout and even after the service year.…”
Section: Discussionmentioning
confidence: 99%
“…The supervision of camp clinics by physicians demonstrates the importance the government places on the health of its Corps members. 9 In the past, Corps members were required to pay for their medical expenses out-of-pocket during the service year. It was, however, a welcome development when the government announced the implementation of the inclusion of Corps members into the NHIS program in 2022 through its group individual and family social health insurance program (GIFSHIP).…”
Section: Discussionmentioning
confidence: 99%